In vivo dosimetry using MOSkin detector during Cobalt-60 high-dose-rate (HDR) brachytherapy of skin cancer - Jamalludin, Zulaikha; Jong, Wei Loong; Ho, Gwo Fuang; Rosenfeld, Anatoly B.; Ung, Ngie Min (Springer, 2019)
The MOSkin, a metal–oxide semiconductor field-effect transistor based detector, is suitable for evaluating skin dose due to its water equivalent depth (WED) of 0.07 mm. This study evaluates doses received by target area and unavoidable normal skin during a the case of skin brachytherapy. The MOSkin was evaluated for its feasibility as detector of choice for in vivo dosimetry during skin brachytherapy. A high-dose rate Cobalt-60 brachytherapy source was administered to the tumour located at the medial aspect of the right arm, complicated with huge lymphedema thus limiting the arm motion. The source was positioned in the middle of patients’ right arm with supine, hands down position. A 5 mm lead and 5 mm bolus were sandwiched between the medial aspect of the arm and lateral chest to reduce skin dose to the chest. Two calibrated MOSkin detectors were placed on the target and normal skin area for five treatment sessions for in vivo dose monitoring. The mean dose to the target area ranged between 19.9 and 21.1 Gy and was higher in comparison with the calculated dose due to contribution of backscattered dose from lead. The mean measured dose at normal skin chest area was 1.6 Gy (1.3–1.9 Gy), less than 2 Gy per fraction. Total dose in EQD2 received by chest skin was much lower than the recommended skin tolerance. The MOSkin detector presents a reliable real-time dose measurement. This study has confirmed the applicability of the MOSkin detector in monitoring skin dose during brachytherapy treatment due to its small sensitive volume and WED 0.07 mm. © 2019, Australasian College of Physical Scientists and Engineers in Medicine.